Boron and phosphorous-doped graphene as a metal-free electrocatalyst for the oxygen reduction reaction in alkaline medium1. Issue 66 (19th July 2015) - Jo, Gayoung; Sanetuntikul, Jakkid; Shanmugam, Sangaraju
<x xml:space="preserve">Abstract</x> Phosphorous and boron-doped graphene, prepared using a single precursor, showed reasonable oxygen reduction activity and excellent stability in alkaline electrolyte.